Systematic Literature Review: Problem-Solving Skills in Physics Learning - Heldalia; Heru Kuswanto; Emil Salim (Postgraduate, University of Mataram, 2025)
This study explores problem-solving skills in physics education by systematically reviewing literature from articles published between 2015 and 2024. The review adhered to the PRISMA-P guidelines and analyzed 18 relevant studies sourced from the Scopus database. The findings reveal that the majority of research focuses on enhancing students' problem-solving abilities, particularly in terms of improving critical thinking, reasoning, and creativity in physics instruction. The integration of technology into teaching methods also emerged as a prominent trend in supporting the development of these skills. High school students were the most common research subjects, followed by college students, underscoring the importance of fostering problem-solving abilities early in education. Furthermore, the study highlights a predominance of quantitative and mixed-methods approaches, suggesting the need for more research into practical classroom applications. The study recommends further investigation into adaptive learning models and calls for more qualitative research to deepen the understanding of problem-solving skills in physics education.